ANALISIS DAYA PESONA WISATA BERDASARKAN PESPEKTIF WISATAWAN PADA TAMAN REKREASI SELECTA KOTA BATU JAWA TIMUR - Marhaeni, Tri; Widjajanti, Roos; Chandra, Edy; Sanjaya, Aprillina (STIA MALANG, 2025)
This research aims to describe the perspective of tourists on the charm of the Selecta Recreational Park tourist attraction, using a qualitative approach. Data with unstructured interviews from 17 informants who have visited the tourist attraction, and analyzed qualitatively. The results obtained indicate that the charm of tourism according to the perspective of tourists is dominated by the charm of nature which is complemented by the charm of man-made attractions, in other words, it refers more to the assessment of service quality that leads to physical evidence that has been provided by tourism services. Recommendations are submitted for tourism managers to maintain the charm of nature and can increase other charms through artificial charms or physical evidence of services that are different from other tourist attractions